2015
DOI: 10.1039/c5ra00856e
|View full text |Cite
|
Sign up to set email alerts
|

One-step synthesis of magnetic 1,6-hexanediamine-functionalized reduced graphene oxide–zinc ferrite for fast adsorption of Cr(vi)

Abstract: A one-step solvothermal method was developed to prepare nearly cubic ZnFe 2 O 4 nanoparticles loaded on 1, 6-hexanediamine-functionalized reduced graphene oxide (HDA-RGO-ZnFe 2 O 4 ) for fast removing Cr (VI). The materials were characterized by transmission electron microscopy, Fourier-transform infrared spectroscopy, X-ray diffraction, Raman, and vibrating sample magnetometry. Experimental results indicated that Cr (VI) adsorption by HDA-RGO-ZnFe 2 O 4 is strongly pH dependent and the adsorption equilibrium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…The measurements of ZF and ZFG nanoparticles showed two distinct peaks at 520 cm −1 and 381 cm −1 . These two peaks correspond to the stretching vibration of the Zn-O bond at the tetrahedral position and the Fe-O bond at the octahedral position, respectively [ 63 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…The measurements of ZF and ZFG nanoparticles showed two distinct peaks at 520 cm −1 and 381 cm −1 . These two peaks correspond to the stretching vibration of the Zn-O bond at the tetrahedral position and the Fe-O bond at the octahedral position, respectively [ 63 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…The observed difference in q m is ascribed to the nature of cations deposited in GNSFs. Similarly, different q m values for Cr(VI) ions observed depending on different types of cations, being 501, 136, and 172 mg g −1 for poly(m-phenylenediamine)/rGO/NiFe 2 O 4 (PmPD/rGO/NFO) (Wang et al, 2017b), amino-functionalized SiO 2 @CoFe 2 O 4 -GO (Santhosh et al, 2017), and 1,6-hexanediamine-functionalized rGO/ZnFe 2 O 4 (HDA-rGO-ZnFe 2 O 4 ) (Li et al, 2015), respectively. Numerous studies have employed bare/polymer-grafted magnetic nanoparticles or similar graphene-based magnetic composites to remediate toxic heavy metals and organic dyes.…”
Section: Adsorption Capacity Of Gnsfs-mentioning
confidence: 99%
“…Wang et al (2017b) reported that the electrostatic interaction between negatively charged Cr(VI) species and the protonated PmPD/rGO/NFO played an important role in Cr(VI) adsorption at pH = 3. Li et al (2015) observed that HDA-rGO-ZnFe 2 O 4 had better removal performances for Cr(VI) under acidic conditions, in which the protonated amine groups (__NH 3 + ) of HDA would attract the negatively-charged Cr(VI) species electrostatically. In addition, the adsorbed Cr(VI) was reduced to Cr(III) and bound to the negatively-charged carboxylic groups of HDA-rGO-ZnFe 2 O 4 through electrostatic interaction, which was confirmed by XPS analysis.…”
Section: Adsorption Mechanisms Of Gnsfs-mentioning
confidence: 99%
“…More recently, a particular interest in the development of visible-light-responsive photocatalysts is the synthesis of nanocrystalline spinel ferrite. Spinel ferrites including NiFe 2 O 4 , ZnFe 2 O 4 and CuFe 2 O 4 have possessed unique photocatalytic properties for the removal of inorganic contaminants, [9][10][11] antimicrobial activity 12 and organic dyes. [13][14][15][16][17] In addition, the spinel crystal structure of ferrites offers the available extra catalytic sites by virtue of the crystal lattices and a band gap capable of absorbing visible light to enhance the photodegradation efficiency of pollutants.…”
Section: Introductionmentioning
confidence: 99%